A Retrospective Analysis of the Efficacy of Pembrolizumab in Melanoma Patients With Brain Metastasis. Issue 3 (April 2017) - Dagogo-Jack, Ibiayi; Lanfranchi, Michael; Gainor, Justin F.; Giobbie-Hurder, Anita; Lawrence, Donald P.; Shaw, Alice T.; Sullivan, Ryan J.
Abstract : A total of 50% of patients with melanoma will develop brain metastasis (BM). Pembrolizumab was approved for treatment of metastatic melanoma on the basis of significant systemic antitumor activity. Because of low enrollment of patients with BM in pembrolizumab trials, efficacy against melanoma BM remains unknown. We reviewed records of 89 consecutive patients with melanoma treated with pembrolizumab at our institution between May 1, 2014 and October 31, 2015 to determine the time to progression. Thirty-six (40%) patients had BM before pembrolizumab. Twenty-six (72%) patients with BM had received prior treatment for BM. With median follow-up of 17.2 months, 54 patients (61%) developed progressive disease on pembrolizumab. Intracranial progression occurred in 19 patients (21%), 3 of whom did not have BM before treatment. Median time to progression at any site was 6 months for those without BM (n=53), 5 months for those with treated BM (n=26), and 1.2 months for patients with untreated BM (n=10). Using a Cox regression model adjusted for baseline factors, there was a statistically significant (Wald χ 2 P =0.003) reduction in the hazard of progression for patients without BM [hazard ratio, 0.19; 90% confidence interval, 0.08–0.42) and patients with treated BM (hazard ratio, 0.27; 90% confidence interval, 0.12–0.64) compared with those with untreated BM. In conclusion, melanoma patients with pretreated BM can have durable systemic responses to pembrolizumab. Large, prospective studies are needed to evaluate the intracranial antitumor activity of pembrolizumab in melanoma patients with untreated BM.